A Review on the Fabrication and Characterization of Titania Nanotubes Obtained via Electrochemical Anodization - Syeda Ammara Batool; Muhammad Salman Maqbool; Muhammad Awais Javed; Akbar Niaz; Muhammad Atiq Ur Rehman (Surfaces, 2022)
Recently, titania nanotubes (TNTs) have been extensively studied because both their functional properties and highly controllable morphology make them important building blocks for understanding nanoscale phenomena and realizing nanoscale devices. Compared with sol–gel and template-assisted methods, electrochemical anodization is a simple, cost-effective, and low-temperature technique offering additional advantages such as straightforward processing and ease of scale-up. This review focuses on the process modalities and underlying mechanism of electrochemical anodization to achieve a different set of TNTs for a variety of applications. Finally, important applications of TNTs are highlighted including biomedical devices, water purification, and solar cells.